Smart object counter - Wong, Chun Foong (Nanyang Technological University, 2021)
Vehicle counting is made possible with the help many advanced computer vision algorithms. This project will be investigating many computer visions models especially destiny map estimation approach such as CSRNet, DMCount, M-SFANet+M-SegNet and etc. after evaluations will be conducted to determine the best approach in vehicle counting. After which, the best models will be implemented into a web-based application that will perform vehicle counts. ReactJS will be used to create a front-end website to display essential data. Next NodeJs and FlaskJs will be used to create back end so that data can be processed before routing it back the front end for display purposes and analysis can be conducted as well. Overall, the objective of the project is finding the best approach to conduct vehicle counting and results are fairly accurate in term of estimation.